2022
DOI: 10.3390/su14116683
|View full text |Cite
|
Sign up to set email alerts
|

Low-Carbon Strategies Considering Corporate Environmental Responsibility: Based on Carbon Trading and Carbon Reduction Technology Investment

Abstract: This paper focuses on the optimal strategic choice of carbon trading and carbon reduction technology investment under the cap-and-trade system. We consider a carbon-dependent production enterprise that trades carbon emission rights or invests in carbon reduction technologies under the regulation of the cap-and-trade system. The enterprise undertakes corporate environmental responsibility (CER) and aims to maximize the comprehensive benefits of both the economy and the environment. Using numerical simulation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Amidst the current climate crisis, organizations that cause substantial environmental pollution could face penalties or even closure. The notion of sustainable development stresses the importance of economically, socially, and environmentally balanced advancements (Axon, 2016;Y. Yuan, Zhang, Wang, & Wang, 2022).…”
Section: Carbon Emission Reduction Performance and Financial Performancementioning
confidence: 99%
“…Amidst the current climate crisis, organizations that cause substantial environmental pollution could face penalties or even closure. The notion of sustainable development stresses the importance of economically, socially, and environmentally balanced advancements (Axon, 2016;Y. Yuan, Zhang, Wang, & Wang, 2022).…”
Section: Carbon Emission Reduction Performance and Financial Performancementioning
confidence: 99%
“…Faı ´sca et al [57] have reported the repurposing of the antimalarial drug, hydroxychloroquine (HCQ), as an efficient antiviral treatment for SARS-CoV-2, using the dicationic family of ILs to enhance the physicochemical properties. N 4 Yuan et al [58] have studied the use of cholinium-amino acid-based ILs (CHAAILs) to improve the solubility and permeation of poorly soluble drugs. The solubility of ferulic acid and puerarin was significantly increased with the addition of only a small amount of CHAAIL.…”
Section: And [Mp][ba]mentioning
confidence: 99%
“…Yuan et al. 58 have studied the use of cholinium‐amino acid‐based ILs (CHAAILs) to improve the solubility and permeation of poorly soluble drugs. The solubility of ferulic acid and puerarin was significantly increased with the addition of only a small amount of CHAAIL.…”
Section: Ils At a Glancementioning
confidence: 99%
“…Research on whether disclosure of corporate environmental performance is useful for investors to evaluate corporate value has long received much attention in the field of environmental accounting [15][16][17][18][19][20][21]. Previous studies have mainly concentrated on the impact of environmental performance on corporate value [21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Backgrounds and Hypothesesmentioning
confidence: 99%